Gerenciamento e Integração das Bases de Dados de Sistemas de Detecção de Intrusões - SILVA, Emanoel Costa Claudino (2006)
The digital security has become an important factor for institutions of diverse domains. The Intrusion Detection Systems (IDS) have appeared as a solution for detention and correction of intrusion of pro-active way. Thus, some models of SDIs have appeared to diminish the probability of compromising of on computational systems connected in net, identifying, reporting and answering to these incidents. In face to that diversity of solutions, they lack proposals of standardization of the information used for these Systems, as well as of mechanisms of interoperability and exchange of information between the solutions in use. This dissertation, proposes a model, an architecture and an implementation of a SDI´s Information Manager, using the technologies of Multi- Agents Systems and Web Services. The objective of the Information Manager is to keep the information that are necessary to the development of the inherent functions of a SDI, in a safe and updated way. We also propose a standard of format for storage of these data to insert requirements in the environment, as: Unified Storage, Transparent Access, Uniform Generation of Data and Friendly Interaction.